Urinary antibiotic level of school children in Shanghai, East China, 2017–2020. (15th December 2021) - Wang, Hexing; Tang, Chuanxi; Wang, Yuanping; Han, Minghui; Jiang, Feng; Jiang, Lufang; Wu, Jingui; Fu, Chaowei; Chen, Yue; Jiang, Qingwu
Abstract: In recent years, an extensive exposure to antibiotics from various sources has been demonstrated in China by the biomonitoring method, but the temporal trend remains little known. The study aim was to explore the temporal trend of exposure to antibiotics and associated health risk in children. A dynamic child cohort was established in Shanghai, East China between 2017 and 2020. A total of 684 school children aged 7-11 years were included, and 280 in 2017, 279 in 2018, 288 in 2019, and 287 in 2020 participated in annual surveys. Twenty-three typical antibiotics and three metabolites from five categories (four tetracyclines, five qinolones, six macrolides, eight sulfonamides, and three phenicols), bisphenol A (BPA), and monobutyl phthalate (MBP) were determined in urine. Logistic regression analysis with generalized estimating equations was conducted to investigate the associations between various variables and the detection frequency of antibiotics in urine. Seventeen antibiotics and three metabolites were found in 51.9% of all urine samples. Compared to 2017, the detection frequency in urine reduced 31.8% in 2020 for all antibiotics (58.2% vs 39.7%) and reduced 36.8%–55.8% for tetracyclines (11.4% vs 7.0%), qinolones (34.3% vs 21.3%), macrolides (8.6% vs 3.8%), sulfonamides (16.4% vs 8.7%), and phenicols (19.3% vs 12.2%). After accounting for personal characteristics, food consumption, and urinary BPA and MBP, a decreasing temporal trend of detection frequencies was observed from 2017 to 2020 for most antibiotics. Urinary concentration, estimated daily intake, and acceptable daily intake-based health risk of antibiotics showed a temporal trend similar to detection frequency. There was an extensive exposure to antibiotics in children. However, a decreasing temporal trend occurred for the exposure during the period from 2017 to 2020. The trend was likely to be caused by decreased antibiotic use and/or decreased residues in food and/or drinking water. Highlights: An extensive exposure to antibiotics presented in children between 2017 and 2020. A decreasing trend of antibiotic exposure occurred in children from 2017 to 2020. Personal characteristics and food consumption seemed not to effect the trend. BPA and MBP in urine were not associated with the trend. Decrease of residues in food and/or water or antibiotic use might cause the trend.